Аналізування методів державного управління профільним навчанням - Волошин, О. П. (Видавництво Львівської політехніки, 2012)
Проаналізовано досвід розвитку профільного навчання в Україні, наведено класифікацію методів управління профільним навчанням задля забезпечення відтворення кадрового потенціалу підприємств, описано методи реалізації і переваги профільного навчання. The experience of specialized education in Ukraine is analyzed in the given article. The classification of methods of profile education management to ensure the reproduction of human resources business is given and methods of implementation and benefits of school education are described.
The analysis of publicmanagement profile specialized education methods
Keywords: профільне навчання; компенсаційний процес; відтворення кадрового потенціалу підприємств; profile education; the compensation process; reproduction of businesses’ human resources